2019
DOI: 10.3389/fpls.2018.01971
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Genetic Diversity to Breed Competitive Biofortified Wheat With Enhanced Grain Zn and Fe Concentrations

Abstract: Breeding wheat with enhanced levels of grain zinc (Zn) and iron (Fe) is a cost-effective, sustainable solution to malnutrition problems. Modern wheat varieties have limited variation in grain Zn and Fe, but large-scale screening has identified high levels of Zn and Fe in wild relatives and progenitors of cultivated wheat. The most promising sources of high Zn and Fe are einkorn (Triticum monococcum), wild emmer (T. dicoccoides), diploid progenitors of hexaploid wheat (such as Aegilops tauschii), T. spelta, T. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 37 publications
5
55
0
Order By: Relevance
“…The wide genetic variability found for Fe and Zn represents an important result in terms of breeding program, since the modern varieties have limited variation [47]. Therefore, this gene pool could be investigated for future QTL mapping and breeding biofortified wheat [47,48]. In relation to the macro-mineral elements, the significant highest and lowest contents were found in 'Saragolla' and 'Core' (425 and 233 mg kg −1 of FW) for Ca, 'Duilio', and 'Ramirez' (5200 and 3148 mg kg −1 of FW) for K, 'Tirex', and 'Ramirez' (1663 and 1295 mg kg −1 of FW) for Mg, and 'Tirex', and 'Duilio' (4071 and 1511 mg kg −1 of FW) for P (Tables 4 and 8).…”
Section: Ash Macro- and Micro-minerals Contentmentioning
confidence: 99%
“…The wide genetic variability found for Fe and Zn represents an important result in terms of breeding program, since the modern varieties have limited variation [47]. Therefore, this gene pool could be investigated for future QTL mapping and breeding biofortified wheat [47,48]. In relation to the macro-mineral elements, the significant highest and lowest contents were found in 'Saragolla' and 'Core' (425 and 233 mg kg −1 of FW) for Ca, 'Duilio', and 'Ramirez' (5200 and 3148 mg kg −1 of FW) for K, 'Tirex', and 'Ramirez' (1663 and 1295 mg kg −1 of FW) for Mg, and 'Tirex', and 'Duilio' (4071 and 1511 mg kg −1 of FW) for P (Tables 4 and 8).…”
Section: Ash Macro- and Micro-minerals Contentmentioning
confidence: 99%
“…In recent years attention has focused in part on the possible development of perennial, herbaceous crops [11], [13], [14], [64] . Expanding development of species such as wild, perennial legumes, into an agroforestry system offers opportunities to enhance food production and possibly reduce the risk of nutrient deficiencies [6], [7], [65], [66] . In this study, we explored differences in nutrient content among perennial and annual wild species of the common bean genus Phaseolus , an important first step towards identifying Phaseolus species that might be good candidates for pre-breeding and/or inclusion in agroforestry and other agricultural systems.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the growing body of literature on ion covariation suggests that ion concentrations are highly dynamic and therefore it will be important for breeders to determine the ion variation and covariation for each species (and possibly across multiple geographic locations). However, the promise of agricultural crops with optimization of multiple ions is obtainable; recently, iron and zinc have been successfully co-selected for increased concentrations in wheat species [66] .…”
Section: Correlations In Mineral and Amino Acid Concentrations Acrossmentioning
confidence: 99%
“…The substantial genetic variation present in wheat serves as raw gene pool for the development of biofortified varieties (Garcia‐Oliveira, Chander, Ortiz, Menkir, & Gedil, 2018; Monasterio & Graham, 2000; Velu et al., 2014). A wide range of genetic variation has been identified in wheat genotypes for Zn content (Amiri, Bahraminejad, Sasani, Jalali‐Honarmand, & Fakhri, 2015; Velu et al., 2018). Exploring wheat gene pool at the Genebank of the International Maize and Wheat Improvement Center (CIMMYT, El Batan, México) indicated a several‐fold variation for grain Fe and Zn in disomic hexaploid bread wheat (Velu et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, high genetic variation has been identified for Zn concentration in bread wheat cultivars (Abdoli, Esfandiari, Alilloo, Sadeghzadeh, & Mousavi, 2019; Khokhar et al., 2018). Identification of genetic variability among wheat genotypes may assist breeding programs to develop high Zn varieties (Velu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%